First report on establishment and characterization of a carcinosarcoma tumour cell line model of the bladder - Johannes Eberhard (Nature Portfolio, 2021)
Abstract Carcinosarcoma of the urinary bladder is a very rare and aggressive subtype of bladder cancer with poor prognosis. Characteristically carcinosarcomas exhibit biphasic nature with both epithelial and mesenchymal differentiation. Limited information is available regarding its clinical features and appropriate treatments due to its rarity. Development of tumour models can further our understanding of bladder carcinosarcoma. We report establishment and characterization of the first-ever bladder carcinosarcoma cell line MaS-3. It is established by the outgrow method from 86 year-old caucasian male who underwent a radical pelvic resection after neoadjuvant radiotherapy. MaS-3 showed carcinosarcoma profile with high conformity with to the original tumour in terms of immunocytochemistry. Proteome analysis also aligned the MaS-3 cell line with the carcinosarcoma specimen rather than corresponding non-malignant tissue. Chemotherapy sensitivity testing revealed a great sensitivity of MaS-3 growth to 5-Fluorouracil, Gemcitabine and Cisplatin, with almost no impact of Irinotecan. Additionally, the suitability of MaS-3 for 3D in vitro experiments was also demonstrated. The newly established cell line MaS-3 shows typical characteristics of the tumour and may thus be a useful in vitro model system for studying the tumour biology and developing future of treatments of this rare but very aggressive entity.